Tax law, religion, and justice: an exploration of theological reflections on taxation - Calhoun, Allen (Law and religion, 2021)
Equity and efficiency -- A society within a society -- Thomas Aquinas : the interplay of natural and positive law -- William of Ockham : repudiation of power and wealth -- Martin Luther's redistributive theology of the Lord's supper -- John Calvin and the challenge of inequality -- Triumph of the economy.